A STUDY ON THE ABILITY OF ENGLISH STUDY PROGRAM STUDENTS IN IDENTIFYING NOUN CLAUSES - Zahara, Aini; Supriusman, Supriusman; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research belongs to descriptive research which uses a quantitative approach. The research was aimed to find out the ability of English study program students in identifying noun clauses. The population of this research was the fifth-semester students of the English study program of FKIP Universitas Riau with a total number of population is 110 students. The number of the sample in this research was 36 students, selected by using the cluster random sampling technique. A multiple-choice question test about noun clauses was used as the instrument which consisted of 30 items. There were eleven forms of noun clauses based on the types of each function of noun clauses. The result of the research shows that the mean score of the students in identifying noun clauses was 64. In brief, the English study program students’ ability in identifying noun clauses was categorized into a good level ability.Key Words: Students’ Ability, Identifying, Noun Clauses